Performative and technical treatments and their effectiveness in designing modular street furniture (Al-Academy, 2025)
This study dealt with the topic of (performative and technical treatments and their effectiveness in designing street furniture units), and the research included four chapters, in which the researcher dealt in the first chapter with the research methodology and the research problem, which was the following question:  What are the performative treatments, in light of which the technology and its effectiveness in designing the industrial product are determined? The importance of the research was determined in shedding light on the performance and technical indicators for the design of street furniture units. The aim of the study is (to reveal the performative and technical treatments in the design of street furniture units). The second chapter (the theoretical framework for the research), which included three sections, the first section was:  Performative treatments and their uses in designing street furniture units, and the second section: Technology and its concept in designing street furniture units. Then this chapter ended with indicators. The third chapter included a descriptive research methodology in analyzing the research sample, and the research population consisted of the products of street furniture units designed by (Rolando Cedeno de la Cruz), and the fourth chapter included the research results, the most important of which are:_The sample models showed harmony and compatibility in the design.